Theoretical and Methodological Foundations for Studying Network Mechanisms of Innovative Development in the Republic of Belarus - S. Y. Solodovnikov (Наука и техника)
The paper considers theoretical and methodological foundations for studying network mechanisms of innovative development in the Republic of Belarus and in order to reach the purpose it is necessary to specify the concept of a systematic approach in the context of the study of the indicated mechanisms and develop a methodology for conducting such investigations. Systematic and historical approaches, principles of synergetics have been used as research methods. The paper substantiates the necessity to study the network mechanisms of innovative development in the Republic of Belarus from the point of view of a systematic approach. In this case, the author has refused traditional contrast of stable, essential, regularly repeating connections and relationships in the system to random, chaotic processes, and he has proceeded from the need to consistently apply a law of hierarchical compensation, as well as taking into account such features of the development of the modern economy as the rapid evolution of network technologies, further development of the risk economy, emergence of new challenges for traditional (including old industrial) industries. This has made it possible to define a systematic approach as a se quential and comprehensive examination of  an object not as isolated  from external  influences, but as half-closed,  but with an approach to an open system in which the synergetic processes generated by evolution of network technologies, development of the risk economy, and emergence of new challenges for industrial production (including traditional ones). It has been established that a consistent and comprehensive review of the network mechanisms of innovative development in the Republic of Belarus requires not only to determine initial categories and concepts, to show general and special determining factors, genesis and development trends, but also to conduct constant monitoring aimed at identifying dynamics of needs and interests of political-economic and economic entities involved in this process, as well as material and social technologies for implementation of the needs and interests.